PERGESERAN NILAI-NILAI RELIGIUS KENDURI DALAM TRADISI JAWA PADA MASYARAKAT PERKOTAAN DI KECAMATAN MARPOYAN DAMAI - Sari, Iis Purnama; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by a shift in people's understanding of religious values or the meaning of feast in the Javanese tradition of urban communities from Marpoyan Damai District. The formulations of the research problems are: (1) How the Shifting of Meaning of Kenduri Religious Values in Javanese Tradition in Urban Communities in Marpoyan Damai District, (2) What factors influence the Shifting of Meaning of Kenduri Religious Values in Javanese Tradition in Urban Communities in Marpoyan Damai District. The research aims: (1) To describe the Shifting of Meaning of Kenduri Religious Values in Javanese Tradition in Urban Communities in Marpoyan Damai District, (2) To determine the Factors of Shifting the Meaning of Religious Values of Kenduri in Javanese Tradition in Urban Communities in Marpoyan District. The research was conducted in Marpoyan Damai District from August 2020 to December 2020. This research is a qualitative descriptive study. With research subjects, namely the entire community of IKJR Community (Riau Family Association) in Marpoyan Damai District and the sample using purposive sampling technique with a sample of 27 people as respondents who have met the characteristics or criteria as a sample. The results obtained in this study are a shift in the meaning of the religious values of kenduri in the Javanese tradition including; there are certain groups that have other interests outside the context of the Javanese tradition of kenduri, the kenduri tradition is not sequential so that the meaning is different, the intention of doing the kenduri tradition is deviating, namely to worship other than Allah SWT. Factors that influence a shift in the religious values of kenduri in the javanese tradition include; changes in the mindset on an increasingly advanced society, education, technological advances, interactions from various cultural backgraounds, the influence of globalization, and ideology.Key Words: Shifthing, Religious Values, and Kenduri